Statistical quality control : strategies and tools for continual improvement - Ledolter, Johannes. (John Wiley and Sons, 1999)
Quality problems and prob,em-solving strategies. Management based on facts: the importance of data and data analysis. Process stabilization: making processes predictable. Improvement through designed experiments. Other useful statistical techniques.